(untitled) (diségno, 2024)
This paper addresses the issues related to contemporary representation for landscape design through significant experiences developed from the 1990s to today, born from the collaboration of architects, landscape designers, and artists such as Yves Brunier, Enric Miralles, Inside Outside (studio founded by Petra Blaisse), Mark Smout, Laura Allen, Teresa Moller Landscape Studio (studio founded by Teresa Moller), Openfabric (studio founded by Francesco Garofalo), 08014 arquitectura (studio founded by Adrià Guardiet and Sandra Torres), Mir (studio founded by Mats Andersen and Trond Greve Andersen). Contemporary trends in landscape design representation include hybridizations aimed at integrating the communicative power of the concept with photography through the expressive value of manual experience; schematic drawings of project management systems; detailed analytical representations of the multiple areas involving the landscape; botanical investigation representations; communicative images to narrate atmospheres, materials, and colors. The analysis of the methods, forms, and language in use allows for probing the expressive potential of representation. Over this time, the methods and tools have changed, but it is possible to trace a common denominator, namely the role of representation in relation to the type of narrative objective. Representation does not manifest itself simply as a product/image but as a process of construction of form and of the design and figurative content.